U.S. Contingent Protection against Honey Imports : Development Aspects and the Doha Round - Nogues, Julio J. (World Bank, Washington, DC, 2014)
On December 10, 2001 the U.S. Department of Commerce (DOC) imposed steep antidumping duties against honey imports from Argentina and China ranging from 32.6 percent to 183.8 percent, and a countervailing duty against Argentina of 5.9 percent. A previous antidumping investigation in 1995 ended with a suspension "agreement" that curtailed U.S. imports from China by around 30 percent. Millions of beekeepers around the world, most of them poor, make a living from honey production, and a free and competitive world market would help raise their standards of living. Nevertheless, the sequential pattern of increasing and widening protectionism followed by the United States, the world's top importer, to include successful exporters under the effects of its contingent protection measures sends a clear message that other countries should think twice before investing in expanding honey exports to the United States. In addition to looking into the trade effects of these contingent protection measures, the author concludes that under the regulatory arrangements of the DOC, Argentina's beekeepers never had a chance of defending themselves. For example, responding to the DOC's lengthy and sophisticated questionnaires that sought to determine cost of production went beyond the capacities of poor beekeepers. In the absence of information, the DOC resorted to evidence presented by the petitioners which was riddled with errors. The available evidence suggests that had beekeepers been capable of responding to the questionnaires, the margin of dumping would had been lower, if at all existent. This and other evidence discussed by the author suggest the urgent need to introduce reforms into the World Trade Organization antidumping and subsidy agreements. At the minimum what is required is a consensus that all respondents be given the same opportunity by the international trade rules. The author argues that at present this is not the case and offers suggestions for reforms.